Entrepreneurship Training for Housewives to Improve the Family Economy in Semparu Kopang Village, Central Lombok - Supratman Supratman; Baiq Herdina Septika; Tama Krisnahadi; Sri Sukarni; Yayang Erry Wulandari (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Entrepreneurship training in Semparu Village, Kopang, Central Lombok, aims to enhance family economies through the empowerment of housewives. This activity involves 20 housewives as direct partners. The implementation method includes preparation and execution phases, where materials are delivered through lectures and question-and-answer sessions to improve understanding of entrepreneurship. The training results show an increase in understanding of business management and practical skills, particularly in the production of papaya crisps, which demonstrate good market potential. Participants, who previously had little economic activity, now have the skills to start their own businesses, create job opportunities, and support community independence and empowerment. Recommendations for the future include ongoing monitoring and mentoring to ensure the application of the knowledge gained in facing business challenges. Additionally, it is recommended to expand similar training to other villages in Central Lombok to increase the broader economic impact. This activity not only facilitates short-term solutions through training but also lays the groundwork for sustainable development that supports economic independence and empowerment in Semparu Village.